Kearifan Lokal dalam Pembelajaran Bahasa Inggris: Sarana Meningkatkan Keterampilan Pelajar Bahasa Inggris Dewasa - Aco Nasir; Andriani Andriani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2020)
This study aims at investigating the effect of the integrated local wisdom on English Learning at university Students. The research employed a quasi-experimental design. The experimental class was taught by implementing the integrated local wisdom on English Learning and the non-experimental class by conventional strategy. The subject was the 152 second semester students of Non-English Language teaching Department, Al Asyariah Mandar University. The sample was randomly selected to be one of the classes into the experimental group and the other one into the control group. Since the statistical assumptions were not fulfilled in this study therefore, the data were analyzed by utilizing non parametric testing: Mann–Whitney U and Kruskall-Wallis. The mean score of the students’ reading comprehension achievement in the end of the study was 79.63 in the experimental group while the mean score of the students’ achievement in control group was 56.76 and the p-value was .000, meaning was smaller than level of significance 0.05 (sig 0.000 < 0.05). The finding showed that the integrated local wisdom on English Learning statistically impacted students’ skill using English as Communication devise in daily life compared to one taught using the Conventional strategy.